Octreotide reduces ischaemia-reperfusion injury in the retina - Celiker, U; Ilhan, N; Ozercan, I; Demir, T; Celiker, H (Wiley, 2002)
Purpose: To investigate the role of octreotide on retinal lipid peroxidation and histopathological changes during ischaemia/reperfusion (I/R). Methods: Three groups of seven pigmented guinea pigs each were formed. These represented a control group, an ischaemia group and an ischaemia/octreotide group. One eye of each animal was selected for histopathological evaluation and the other for biochemical assay. Bilateral pressure-induced retinal ischaemia was instigated for 90 min and was followed by 24 hours of reperfusion. Animals in the ischaemia/octreotide and ischaemia groups received either 10 mug/kg of octreotide or saline, repeated five times at 6-hourly intervals, with the first dose administered 15 min prior to the ischaemic insult. Retinal malondialdehyde (MDA) levels and the thickness of the retinal layers were measured. These were compared with equivalent measurements of the control group. Results: The mean MDA level increased in the ischaemia group (p < 0.01) but not in the octreotide group (p > 0.05). Significant increases in the thickness of the overall retina (p < 0.01), inner retina (p < 0.05) ganglion cell layer (p < 0.01) inner plexiform layer (p < 0.01) and inner nuclear layer (p < 0.01) were observed in the ischaemia group. No significant difference in thickness was found in any of the layers in the ischaemia/octreotide group. Conclusion: Octreotide reduces the increases in retinal MDA levels and retinal thickness observed during I/R.
Keywords: retina; ischaemia; reperfusion; lipid peroxidation; octreotide